Cordon Gris: integrated solution for meal recommendation - Ribeiro, J.; Ribiero, D.; Schwarz, A.; Vasconcelos, M. J.; Gerardo, F.; van Harten, C.; Succu, R.; Davison, R.; Oliveira, T.; Silva, T.; Silva, M. (2018 IEEE International Conference on Pervasive Computing and Communications Workshops (PerCom Workshops), 2018)
Malnutrition is known to be a major concern among older adults. Whether is it because social-economic reasons or low nutritional knowledge, older adults typically struggle to have an healthy, varied, and affordable diet. There are already some solutions in the market that try to raise awareness to people's bad habits or to guide them towards more healthy eating ones. However, such solutions do not address the particular needs of older adults or are limited in scope. Automatic solutions for recommending meals can help in this regards; however, designing a meal recommendation system for older adults requires special care in terms of nutritional requirements, as well as a dedicated user interface and service design. The solution here proposed aims to create a unified system for assisting older adults with the planning of meals and shopping, by offering personalized meal recommendations that integrate with external food provisioning services for the delivery of products.